Cooperative learning index card match model to improve the result of Qur’an Hadith learning - Khusnaini Fauzi (Prodi PGMI IAIN Salatiga, 2017)
AbstractLearning result of al-Qur’an Hadith was low, the percentage only reach 25%. The researcher choose the cooperative learning index card match model as one solution. The purpose of this research is to know learning result of al-Qur’an Hadith, especially to understand the contents of the womb QS. Al-Qari’ah and al-Zalzalah which contains the law of nature phenomenon at the students in class IX A of MTs Negeri Kedu. This research was done by two cycles, each cycle contains of three meeting. At the first cycle used cooperative learning index card match model but the students were not divided in groups, consequently the students felt interest but learning result was not maximally reached. After reflecting result at the first cycle, therefore cooperative learning index card match model was applied at the second cycle by dividing two groups and each group consist 14 students with the same subject. The source of data taken from result of observation teacher’s and students’, interview with students, and the test result (pretest and posttest). The results of this research indicates that learning result improvement was that the average of range reaches 11. 79 from 66.07 at the first cycle to 77. 86 at the second cycle. Otherwise, the increasing of the goal result is 33% from 46% at the first cycle to 79% in the second cycle. Keywords: Learning result, cooperative learning, index card match model AbstrakHasil belajar al-Qur’an Hadis rendah, yaitu persentase ketuntasannya hanya mencapai 25%. Peneliti memilih model pembelajaran kooperatif tipe index card match sebagai salah satu solusinya. Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar al-Qur’an Hadis materi memahami isi kandungan QS. Al-Qari’ah dan al-Zalzalah tentang hukum fenomena alam pada siswa kelas IX a MTs Negeri Kedu. Penelitian ini dilaksanakan dalam dua siklus dan masing-masing siklus terdiri atas tiga pertemuan. Siklus 1 menggunakan model pembelajaran kooperatif tipe index card match dimana siswa belum dibagi dalam kelompok, ternyata siswa sudah merasa tertarik namun hasil belum maksimal. Setelah hasil refleksi di siklus 1, maka model pembelajaran index card match di siklus 2 dikemas dalam dua kelompok yang setiap kelompoknya terdiri dari 14 siswa dengan materi yang sama. Sumber data berasal dari hasil observasi guru dan siswa, wawancara dengan siswa, serta hasil tes (pre tes maupun pos tes). Hasil penelitian ini menunjukkan peningkatan hasil belajar siswa berupa rata-rata kelas siswa sebesar 11,79 dari 66,07 pada siklus 1 menjadi 77,86 pada siklus 2. Selain itu juga terjadi peningkatan hasil ketuntasan belajar siswa sebesar 33% dari 46% pada siklus 1 menjadi 79% pada siklus 2. Kata kunci: hasil belajar, pembelajaran kooperatif, model index card match